Research handbook on warfare and artificial intelligence - Geiss, Robin; Lahmann, Henning Christian, 1981- (Edward Elgar Publishing Limited, 2024)
"The Research Handbook on Warfare and Artificial Intelligence provides a multi-disciplinary exploration of the urgent issues emerging from the increasing use of AI-supported technologies in military operations. Bringing together scholarship from leading experts in the fields of technology and security from across the globe, it sheds light on the wide spectrum of existing and prospective cases of AI in armed conflict. Providing critical perspectives on the future of AI and warfare, this Research Handbook advances important debates surrounding technology and its strategic and humanitarian implications. Contributing authors discuss topics including machine learning algorithms in decisions on the use of force, the definition and feasibility of 'meaningful human control', issues pertaining to data protection and privacy, and states' positive obligations when deploying such systems. Ultimately, the book provides critical insights into one of the most contentious debates of our time and poses vital questions for the future of armed conflict. Tackling practical issues in a detailed and engaging manner, this Research Handbook is an indispensable resource for students and scholars of international law, political science, technology and security studies. Its examination of crucial legal, ethical and political issues pertaining to the topic will also make it an invaluable read for policymakers, and researchers at NGOs and think tanks"--